Efektivitas Media Video dan Leaflet terhadap Tingkat Pengetahuan dan Sikap tentang Menstrual Hygiene di MA Darul Ulum Palangka Raya: The Effectiveness of Video Media and Leaflets on Knowledge Level and Attitude about Menstrual Hygiene in MA Darul Ulum Palangka Raya - Herlinadiyaningsih Herlinadiyaningsih; Greiny Arisani (Jurnal Surya Medika (JSM), 2022)
According to the Indonesian Demographic Health Survey in 2017, the behavior of adolescent girls in maintaining hygiene during menstruation was still poor, namely 63.9%; the cause was due to lack of knowledge and information about personal hygiene during menstruation. In fact, during menstruation, fungi, bacteria, and viruses can easily cause reproductive tract infections. Therefore, good menstrual hygiene is very necessary during menstruation. Health education with media aids is important to help as many senses users as possible. Objective: To determine the effectiveness of video media and leaflets on the level of knowledge and attitudes about menstrual hygiene at MA Darul Ulum Palangka Raya. Methods: This study used a quasi-experimental research design with a two-group pretest and posttest design. The number of research samples was 64 young women taken by purposive sampling and divided into experimental and control groups. The statistical analysis test used the Wilcoxon and Mann-Whitney tests. The results showed that the average knowledge of the video group was 68.75 pretest and 88.59 post-test, with the results of the paired t-test with a p-value of 0.000. The mean attitude of the pretest was 51.19, and the post-test was 66.97. And in the leaflet group, the average knowledge of the pretest was 69.38, and the post-test was 86.25. The mean attitude of the pretest was 52.06, and the posttest was 64.94, with the result of the Wilcoxon test with a p-value of 0.000. So, there are significant differences in knowledge and attitudes toward menstrual hygiene before and after the intervention with video and leaflet media. Conclusion: There is no significant difference in the mean, with the results of the gain of knowledge score in the video group of 36.33 and in the leaflet group of 28.78 and the results of the Mann-Whitney test with a p-value of 0.103. So video media and leaflets are equally effective in increasing knowledge and attitudes toward menstrual hygiene. Still, health education using video media is more effective even though the results of statistical tests show less significance.